2010
DOI: 10.1021/tx900367p
|View full text |Cite
|
Sign up to set email alerts
|

Human Liver Microsomal Cytochrome P450 3A Enzymes Involved in Thalidomide 5-Hydroxylation and Formation of a Glutathione Conjugate

Abstract: (R)-Thalidomide was oxidized to 5-hydroxythalidomide and 5’-hydroxythalidomide by NADPH-fortified liver microsomes from humans and monkeys. (R)-Thalidomide was hydroxylated more efficiently than (S)-thalidomide. Recombinant human P450s 3A4, 3A5, and 3A7 and monkey P450s 3A8 and 3A5 (co-expressed with NADPH-P450 reductase in bacterial membranes) also catalyzed (R)-thalidomide 5-hydroxylation. Purified human P450s 2C19, 3A4, and 3A5 mediated (R)-thalidomide 5-hydroxylation at similar rates in reconstituted syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(85 citation statements)
references
References 32 publications
(57 reference statements)
4
81
0
Order By: Relevance
“…In Vitro Enzymatic Assays of SfmD-The assay conditions used to test whether SfmD is a heme-containing oxygenase are similar to the assay conditions that reported for heme-containing oxygenases in the presence of oxygen, such as conditions for cytochrome P450 (18), secondary amine oxygenase (19), heme oxygenase (20), prostaglandin H Synthase (21), and tryptophan 2, 3-dioxygenase TioF (22).…”
Section: Methodsmentioning
confidence: 99%
“…In Vitro Enzymatic Assays of SfmD-The assay conditions used to test whether SfmD is a heme-containing oxygenase are similar to the assay conditions that reported for heme-containing oxygenases in the presence of oxygen, such as conditions for cytochrome P450 (18), secondary amine oxygenase (19), heme oxygenase (20), prostaglandin H Synthase (21), and tryptophan 2, 3-dioxygenase TioF (22).…”
Section: Methodsmentioning
confidence: 99%
“…11,12 Also, the second oxidation step involves a reactive intermediate, possible an arene oxide that can be trapped by GSH to give GSH adducts. 13 Two aspects of in vivo drug interaction of thalidomide were reported: 14 an enhanced clearance of midazolam and a higher area under the curve of 4 hydroxymidazolam following pre treatment with thalidomide in humanized liver mice, presumably due to human P450 3A induction. Although induction of total P450 contents by thalidomide in rat livers have been reported, 15 apparently no interaction of thalidomide has been shown with ethinyl estradiol (P450 3A4 substrate and inhibitor) in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Although the limb buds of both species appeared grossly normal, in situ hybridization revealed that the limb differentiation factor FGF-10 was severely downregulated in rabbit embryos, but not rat embryos, exposed to equivalent concentrations of thalidomide in WEC. Recent identification of a thalidomide-GSH conjugate in human liver microsomes (Chowdhury et al, 2010) provides additional support for the validity of the Hansen et al (1999) WEC findings in the mechanism of thalidomide-induced teratogenicity.…”
Section: Use Of Wec In the Rabbitmentioning
confidence: 79%